Sex-specific regulation of development, growth and metabolism. (30th March 2023) - Shingleton, Alexander W.; Vea, Isabelle M.
Abstract: Adult females and males of most species differ in many aspects of their morphology, physiology and behavior, in response to sex-specific selective pressures that maximize fitness. While we have an increasingly good understanding of the genetic mechanisms that initiate these differences, the sex-specific developmental trajectories that generate them are much less well understood. Here we review recent advances in the sex-specific regulation of development focusing on two models where this development is increasingly well understood: Sexual dimorphism of body size in the fruit fly Drosophila melanogaster and sexual dimorphism of horns in the horned beetle Onthophagus taurus . Because growth and development are also supported by metabolism, the regulation of sex-specific metabolism during and after development is an important aspect of the generation of female and male phenotypes. Hitherto, the study of sex-specific development has largely been independent of the study of sex-specific metabolism. Nevertheless, as we discuss in this review, recent research has begun to reveal considerable overlap in the cellular and physiological mechanisms that regulate sex-specific development and metabolism.